2009
DOI: 10.1074/jbc.m808186200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of the Type II Fructose-1,6-bisphosphatase GlpX from Escherichia coli

Abstract: Gluconeogenesis is an important metabolic pathway, which produces glucose from noncarbohydrate precursors such as organic acids, fatty acids, amino acids, or glycerol. Fructose-1,6-bisphosphatase, a key enzyme of gluconeogenesis, is found in all organisms, and five different classes of these enzymes have been identified. Here we demonstrate that Escherichia coli has two class II fructose-1,6-bisphosphatases, GlpX and YggF, which show different catalytic properties. We present the first crystal structure of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 61 publications
4
85
2
Order By: Relevance
“…This is in agreement with the fact that no bacterial genome has been described as carrying a combination of classes I and III (34). Also, it has been reported that some E. coli strains carry two class II FBPases (GlpX and YggF [56]), but genomic analysis of all phosphatases in B. abortus failed to identify clear candidates for any phosphatase close to GlpX and Fbp (see Fig. S4 in the supplemental material).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is in agreement with the fact that no bacterial genome has been described as carrying a combination of classes I and III (34). Also, it has been reported that some E. coli strains carry two class II FBPases (GlpX and YggF [56]), but genomic analysis of all phosphatases in B. abortus failed to identify clear candidates for any phosphatase close to GlpX and Fbp (see Fig. S4 in the supplemental material).…”
Section: Discussionsupporting
confidence: 69%
“…The existence of a third FBPase is the first and most obvious possibility. So far, five different types of FBPases (I to V) in prokaryotes have been described (56). Whereas FBPases of classes IV and V are restricted to Archaea and their close hyperthermophilic Aquifex bacterial group, many bacteria have dual combinations of class I (Fbp homologues), class II (GlpX homologues), and class III FBPases (34,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycle is similar to that found in many other organisms, except no gene for sedoheptulose-1,7-bisphosphatase was found in R. rubrum. However, in many organisms the fructose-1,6-bisphosphatases, especially of the class II type, also have sedoheptulose-1,7-bisphosphatase activity (1,3,55,59,69), and a cbbF homolog in R. rubrum, Rru_A2409 (glpX), is predicted to be of this type.…”
Section: Resultsmentioning
confidence: 99%
“…The third block is part of the Li ϩ -sensitive phosphate motif and was shown previously by crystallographic and mutagenesis studies to be important but not sufficient for metal ion binding and catalysis (51). While FBPase II enzymes from E. coli (52), M. tuberculosis (50), Synechocystis sp. PCC6803 (25), B. subtilis (33), and C. glutamicum (42) have been biochemically characterized, the characteristics of a promiscuous FBPase/SBPase from a nonphotosynthetic bacterium lacking the Calvin cycle have not yet been determined.…”
Section: Bioinformatic Analysis and Phylogeny Of The Fbpases Glpxmentioning
confidence: 99%